Leadership culture and implementation of county integrated development plan in Western Counties, Kenya - Leonard, Momos (Papanda Publisher, 2024)
In Kenya, the County Governments are required by planning and budgeting guidelines (URT, 2011) to have five years strategic plans (CIDP) which all the counties comply. However, its implementation is always not effective. The rationale of this cram was to study the role of organizational culture on implementation of county integrated development plans in devolved governments in western region Kenya. The selection of this subject was discriminatory by the reality that implementation of County Integrated Development Plan in the Counties in Western Region has been an issue for the last ten years. The aim of the study was to establish the effect of leadership culture on implementation of County Integrated Development Plans in devolved units of Western Region. The research used descriptive study design to gather information on the role of leadership culture on implementation of CIDP and was guided by balanced scorecard theory. A sample size of 364 and questionnaires was used in data collection. The research instrument was constructed based on the constructs identified in the conceptual framework. Both descriptive and inferential statistics were used to analyze the data. Data analysis was done using multi hierarchical regression model. Mean and standard deviation was also calculated and the results presented in form of tables. The findings of the study showed that leadership culture had a significant impact on CIDP implementation where the correlation coefficient (R) of 0.492 established a fair linear correlation linking leadership culture and CIDP Implementation among the devolved units of Western Region Counties. Leadership culture explained 24.2% of the variance in CIDP implementation in devolved units of Western Region as signified by R- square of 0.242. The significance value was 0.000<0.05. This showed that the model was statistically significant in predicting the influence of leadership culture on implementation of CIDP among the devolved units of Western Region. County Governments ought to look into their leadership culture as it positively influences the implementation of CIDP. Leadership culture comprises of vision and values, communication, empowerment and trust, decision-making, accountability and performance and development and learning. Additionally, granting a decision-making authority, access to information, collaboration and participation, skill development and training, recognition and rewards and supportive leadership contributes to enhanced CIDP implementation in County Governments across the Country.